2013
DOI: 10.1186/cc12606
|View full text |Cite
|
Sign up to set email alerts
|

Hepatic excretory function in sepsis: implications from biophotonic analysis of transcellular xenobiotic transport in a rodent model

Abstract: IntroductionHepatobiliary elimination of endo- and xenobiotics is affected by different variables including hepatic perfusion, hepatocellular energy state and functional integrity of transporter proteins, all of which are altered during sepsis. A particular impairment of hepatocellular transport at the canalicular pole resulting in an accumulation of potentially hepatotoxic compounds would have major implications for critical care pharmacology and diagnostics.MethodsHepatic transcellular transport, that is, up… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
17
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(20 citation statements)
references
References 23 publications
2
17
1
Order By: Relevance
“…They have shown previously that hepatocellular transport at the canalicular pole of the hepatocyte is impaired in sepsis, with the result that a spectrum of hepatotoxic materials accumulates within the septic liver. They now extend these important observations [1]. …”
supporting
confidence: 77%
See 1 more Smart Citation
“…They have shown previously that hepatocellular transport at the canalicular pole of the hepatocyte is impaired in sepsis, with the result that a spectrum of hepatotoxic materials accumulates within the septic liver. They now extend these important observations [1]. …”
supporting
confidence: 77%
“…A new report by Gonnert and co-workers from the Center for Sepsis Control and Care in Jena Germany, recently appearing in Critical Care , provides important new insight into the nature and mechanisms of hepatocellular dysfunction in sepsis [1]. Since Bywaters first described the phenomenon of jaundice following severe trauma in 1946 [2], liver dysfunction has been considered a prominent feature of the Multiple Organ Dysfunction Syndrome and has been defined predominantly by hyperbilirubinemia and clinical jaundice [3-6].…”
mentioning
confidence: 99%
“…[24] In addition, considering hypoglycemia is a frequent event in liver failure, the close monitoring of blood glucose levels and careful glucose administration are required, and intensive insulin therapy should then be used with caution.…”
Section: Therapeutic Considerations For Sepsis-associated Liver Dysfumentioning
confidence: 99%
“…There is a substantial need for an effective therapy that will decrease the morbidity and mortality associated with sepsis. The liver is a critical organ for host survival in response to sepsis through its role in scavenging bacteria and producing inflammatory mediators; however, it might also become damaged in the pathogenesis of sepsis as the result of a dysregulated inflammatory response (Recknagel et al ; Gonnert et al ). Clinical evidence has shown that hepatic dysfunction is an early event in sepsis and is a specific risk factor for poor outcome (Kramer et al ).…”
Section: Introductionmentioning
confidence: 99%